2016
DOI: 10.1097/md.0000000000003034
|View full text |Cite
|
Sign up to set email alerts
|

Parental Use and Educational Campaigns on Sunbed Use Among Teenagers and Adolescents

Abstract: This study aimed to evaluate the prevalence of sunbed use among teenagers and the association between familial behavior and the adoption of UV-protective practices in this age group. We also assessed the impact of an educational program on students’ knowledge about the potential risks of sunbed use. The educational intervention focused on: (i) skin effects of UV radiation, (ii) photoaging and photocarcinogenesis, (iii) risk factors for skin cancer, (iv) indoor sun tanning and misleading concepts such as possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
4
16
1
1
Order By: Relevance
“…Nonetheless, there still is a lack of reliable data on the profiles and motivation of the remaining users despite the clear‐cut public awareness campaigns. Finally, there is a need for continued awareness campaigns on the risks of sunbed use as performed in several countries, which should focus on especially young persons but also their social environment . There is a need for further data on specifying the attributable risk in those minorities who still use sunbeds on a regular basis.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, there still is a lack of reliable data on the profiles and motivation of the remaining users despite the clear‐cut public awareness campaigns. Finally, there is a need for continued awareness campaigns on the risks of sunbed use as performed in several countries, which should focus on especially young persons but also their social environment . There is a need for further data on specifying the attributable risk in those minorities who still use sunbeds on a regular basis.…”
Section: Resultsmentioning
confidence: 99%
“…Female students in our study proved to be more prone to using a sunbed than male – not only they use it more often, but also they plan to use them more frequently in the future. The female aspiration to intentional tanning in order to enhance attractiveness has been described in recent literature across Europe . Also, younger students consider the sunbeds not to be so harmful and tend to start with the sunbeds at a younger age, a phenomenon already registered in different countries …”
Section: Discussionmentioning
confidence: 88%
“…The female aspiration to intentional tanning in order to enhance attractiveness has been described in recent literature across Europe. [27][28][29][30] Also, younger students consider the sunbeds not to be so harmful and tend to start with the sunbeds at a younger age, a phenomenon already registered in different countries. 28,29 The third set of questions regarding behaviour in the sun showed that many adolescents (43.71%) spend more than 1 h in the sun without any protection, which is still less compared to Greek peers -60.2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggests that parents generally play a role in inhibiting – or in some cases facilitating – indoor tanning behavior. 16,24 Studies find that young women who tanned the first time with their mother – typically as adolescents – are more likely to become higher frequency tanners than those that did not. 25,26 Therefore, for some adolescents, tanning for the first time with their mother may signify a ‘stamp of approval’ on the behavior that leads to more frequent and casual use of tanning beds.…”
Section: Discussionmentioning
confidence: 99%